2016
DOI: 10.1111/aogs.12862
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of antenatal anemia in a Scottish population: a retrospective cohort study

Abstract: This study shows the incidence of antenatal anemia is decreasing steadily within this Scottish population. However, given that anemia is a readily correctable risk factor for major causes of morbidity and mortality in the UK, further work is required to investigate appropriate preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 14 publications
5
64
0
2
Order By: Relevance
“…During pregnancy, a lot of physiologic changes occur to accommodate the demands of the developing fetus, which affects the hematologic parameters directly or indirectly. These hematologic changes are considered to be the risk factors affecting maternal and pregnancy outcome . For hematologic complication that can be discriminated and treated early, it is important to know the variation during the entire stages of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, a lot of physiologic changes occur to accommodate the demands of the developing fetus, which affects the hematologic parameters directly or indirectly. These hematologic changes are considered to be the risk factors affecting maternal and pregnancy outcome . For hematologic complication that can be discriminated and treated early, it is important to know the variation during the entire stages of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…These hematologic changes are considered to be the risk factors affecting maternal and pregnancy outcome. [5][6][7][8] For hematologic complication that can be discriminated and treated early, it is important to know the variation during the entire stages of pregnancy. Thus, to understand the changes better and distinguish whether it caused by physiologic or pathologic, there is a basic need *These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have investigated point estimates of Hb and anaemia in pregnancy and outcomes. Anaemia and low Hb in the pregnancy period have been linked to a higher risk of transfusion , preterm birth , SGA and admissions to neonatal intensive care units . A meta‐analysis of cohort studies has also confirmed a significant increase in the risk of preterm birth with anaemia in the first or second trimester .…”
Section: Discussionmentioning
confidence: 91%
“…Anaemia has been associated with adverse outcomes including low birthweight and preterm birth and with an increased risk of blood transfusion . However, there is a lack of data on natural Hb trajectories during pregnancy and how these are associated with adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Ezzati et al (2002) find that South Asia accounts for about one-half of global maternal deaths due to anemia, and India accounts for about 80% of the South Asian total. In 1990, 19% of the maternal deaths in India were related to anemia (Anand, 1995), which also contributes to maternal deaths caused by hemorrhage, septicemia, and eclampsia (Rukuni et al 2016).…”
Section: Introductionmentioning
confidence: 99%